2015
DOI: 10.1111/ajsp.12117
|View full text |Cite
|
Sign up to set email alerts
|

The effect of geographic indication in advertising background pictures on product evaluation: The moderating role of familiarity

Abstract: This study investigates whether geographic indications in the backgrounds of advertising pictures might affect the viewer's evaluation of a product. The findings reveal that participants in the proximal geographic indication evaluated the product more favourably than those in the distal geographic indication when they were exposed to feasibility-related information. By contrast, participants in the distal geographic indication evaluated the product more favourably than those in the proximal geographic indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…Aggarwal and Zhao (2015) demonstrated that participants in a global level (vs local level) showed a lesser preference for a new computer desk with feasibility-related features. Kim, Sung, Lee, Choi and Sung (2016) and Kim, Song, and Yeo (2016) also demonstrated that participants with local processing responded more favorably to concrete feasibility messages. Thus, activating local processing is more likely to increase the importance of concrete feasibility messages rather than the importance of abstract desirability messages.…”
Section: Persuasive Messagementioning
confidence: 90%
See 1 more Smart Citation
“…Aggarwal and Zhao (2015) demonstrated that participants in a global level (vs local level) showed a lesser preference for a new computer desk with feasibility-related features. Kim, Sung, Lee, Choi and Sung (2016) and Kim, Song, and Yeo (2016) also demonstrated that participants with local processing responded more favorably to concrete feasibility messages. Thus, activating local processing is more likely to increase the importance of concrete feasibility messages rather than the importance of abstract desirability messages.…”
Section: Persuasive Messagementioning
confidence: 90%
“…simple touch control, easy portability and quickly accessible connectivity) and abstract desirability messages (e.g. improved multitasking, multi-media applications and high processing performance) were composed with reference to a study by Kim, Song and Yeo (2016). Participants were then instructed to examine the ads for 2 min.…”
Section: Studymentioning
confidence: 99%
“…To obtain GI certification, small producers must not only improve production processes, but also organize collectively to create and maintain norms identifying the product to be certified (Kim et al, 2016;Vieira & Pellin, 2015).…”
Section: Geographical Indicationmentioning
confidence: 99%
“…Although it covers only a small group, the current membership of the CCCA sees such an associative organization to be a place where artisanal curd cheese producers can obtain specific membership benefits (Kim et al, 2016). To confront problems related to product quality and increase financial gains among association members, coordinated efforts on the part of dairy farmers and cheese producers are viewed as being the most effective form of organization:…”
Section: Meaning Of Curd Cheese Production: Role Of the Certificationmentioning
confidence: 99%
See 1 more Smart Citation